Elevating Educational Quality: The Synergistic Impact of Principal Supervision, Learning Environment, and Teacher Pedagogy - Yesi Elfisa; Diva Apri Mulya; Muhammad Ali Imron; Shobrina Fitri; Zamdani Zamdani (Journal of General Education and Humanities, 2026)
Improving learning quality in Integrated Islamic Elementary Schools (SDIT) in Merangin Regency requires principal academic supervision, a supportive learning environment, and teachers’ pedagogical competence. This quantitative ex post facto survey examined the extent to which these three variables predicted learning quality. Data were collected from 86 teacher respondents through a Likert-type questionnaire using saturated sampling of the accessible SDIT teacher population. The data were analyzed using descriptive statistics, assumption tests, simple linear regression, multiple linear regression, t-tests, an F-test, and coefficients of determination. The results show that principal academic supervision significantly predicted learning quality (R² = 0.232 or 23.2%), the learning environment significantly predicted learning quality (R² = 0.264 or 26.4%), and Teacher Pedagogical Competence was the strongest individual predictor (R² = 0.298 or 29.8%). Simultaneously, the three predictors explained 46.5% of the variance in learning quality. These findings indicate that learning quality is associated with the combined strengthening of instructional leadership, school learning conditions, and teacher pedagogical capacity.